The Grundriss Der Sozialokonomik - Day, Clive; Albrecht, G. (Quarterly Journal of Economics, 1926)
Journal Article The Grundriss der Sozialökonomik Get access Clive Day Clive Day Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 41, Issue 1, November 1926, Pages 171–174, https://doi.org/10.2307/1885559 Published: 01 November 1926